FE Analysis and experimental validation of land subsidence due to ground water level variation - Fahmi, Ahmad; Dabbagh, Jamal; Moezzi, Meysam (International Journal of Engineering and Technology, 2015)
Variation in groundwater with excessive withdrawal is one of the causes of land subsidence. Withdrawal of groundwater level can cause an increase in effective stress at thick clay layers, leading to land subsidence. In Rafsanjan plain in Iran, due to the excessive use of groundwater, land subsidence has caused earth fissures and damages to the buildings and installations. Variation in water table level may happen due to the seasonal extraction of groundwater in spring and summer for farming and replacement due to rainfall in fall and winter. The behavior of soils due to the rise of ground water table is non-linear; therefore, a part of settlements may not be recoverable and therefore, it must be considered in the analysis. Modeling of this phenomenon and formulation was considered by finite element method in this research. Finite Element method was used based on element equilibrium and fluid continuity equations. The nonlinear behavior of soil was applied by the bilinear model. The rate of settlements and variation in pore pressure caused by the oscillation of groundwater table were determined by using this model. A good correlation was observed between the results of finite element model and actual data in Rafsanjan area in Kerman Province.